Metroburbia, USA - Knox, Paul L. (Book collections on Project MUSE., 2008)
Decades of economic prosperity in the United States have redefined the American dream. Paul Knox explores how extreme versions of this dream have changed the American landscape. Increased wealth has led America?s metropolitan areas to develop into vast sprawling regions of?metroburbia??fragmented mixtures of employment and residential settings, combining urban and suburban characteristics. Upper-middle-class Americans are moving into larger homes in greater numbers, which leads Knox to explore the relationship between built form and material culture in contemporary society. He covers changes.